MgCO? contents of the fibrous dolomite crystals in methane seep carbonates from Marmorito, northwest Italy - Yang Lu; Carsten Paulmann; Boriana Mihailova; Thomas Malcherek; Daniel Birgel; Matthias López Correa; Zhiyong Lin; Liuyi Lu; Yvonne Milker; Jörn Peckmann (PANGAEA, 2023)
Samples were made into thin sections with polished surface. Each spectrum was measure by 10 loops with each one collected for 15 seconds.
In: Lu, Y et al. (2023): MgCO? contents, structure, and carbon and oxygen isotope compositions of fibrous crystals in a Miocene methane seep carbonate [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.963595